The Impact of Augmented Reality on Data-Driven Innovation Capabilities In Enhancing Customer Interaction: An Applied Study - Khalid Kadhim Mohammed (Indonesian Journal Publisher, 2025)
The research aims to measure the impact of augmented reality on data-driven innovation capabilities (DDI) in enhancing Customer Interaction (CI) among employees at Nour Al-Kafeel Company, as the research variables represent an aspect that has not been sufficiently studied in the current literature. This objective was set to address the problem faced by the company, which was formulated in an important question: (Is there an impact of augmented reality on DDI in enhancing CI among the company's employees?). To address the problem, the research developed a questionnaire tool to collect the necessary data about employees and the levels of the research variables. A total of 100 survey forms were distributed, of which 83 were returned, 7 of them damaged and 76 valid for analysis, resulting in a response rate of 76%. For data analysis, the statistical package (SPSS & AMOS) was used, and after the analysis, the results showed that there is a correlation and influence between augmented reality, DDI, and CI. This highlights Noor Al-Kafeel Company's interest in revealing information related to its products by granting customers the right to compensation and discounts when exposed to the resulting risks. Noor Al-Kafeel Company is also keen to enhance CI by revealing innovation marketing ideas, which motivates customers to engage, repeat purchases, and enrich themselves with sufficient information about these products, encouraging them to try and satisfy their intrinsic desires. Based on this, the study recommended that Noor Al-Kafeel Company focus on using the principles of motivation, compensation, and rewards by investing in innovation ideas that lead to development and steering the company to safety, making it a leading company in the labour market and the first among competing companies in the same sector, which directs the maximum possible number of customers towards adopting and using its products available in the labour market.